Overcoming Cancer Drug Resistance Utilizing PROTAC Technology - Burke, Matthew R.; Smith, Alexis R.; Zheng, Guangrong (Frontiers in Cell and Developmental Biology, 2022)
Cancer drug resistance presents a major barrier to continued successful treatment of malignancies. Current therapies inhibiting proteins indicated in cancer progression are consistently found to lose efficacy as a result of acquired drug resistance, often caused by mutated or overexpressed protein targets. By hijacking the cellular ubiquitin-proteasome protein degradation machinery, proteolysis-targeting chimeras (PROTACs) offer an alternative therapeutic modality to cancer treatment with various potential advantages. PROTACs specific for a number of known cancer targets have been developed in the last five years, which present new options for remission in patients with previously untreatable malignancies and provide a foundation for future-generation compounds. One notable advantage of PROTACs, supported by evidence from a number of recent studies, is that they can overcome some of the resistance mechanisms to traditional targeted therapies. More recently, some groups have begun researching the use of PROTACs to successfully degrade mutated targets conferring cancer resistance against first-line treatments. In this review, we focus on analyzing the developments in PROTACs geared towards cancer resistance and targets that confer it in the search for new and successful therapies.